Game Edukasi Bahasa Sumbawa Indonesia Untuk Anak Usia Dini Berbasis Android - Erwin Mardinata; Nora Dery Sofya; Shinta Esabella; Fatihhurroyyan; Bayu Fajar Pratama (Bulletin of Information Technology (BIT), 2023)
The Android-based Sumbawa Early Childhood Education Game was successfully built using Adobe Illustrator for graphic design, Unity for the game engine, and Visual Study Code as a text editor. This educational game has two main menus, namely the learning menu with nine sub-category menus and the second main menu, namely the quiz menu. Games that are designed with attractive images and interactive audio are built using prototype software development methods and application testing using black boxes. Based on the results of application testing, all the features contained in the application run well and according to their functions. Interactive applications such as educational games are a means that can be optimized to improve children's motor development. Thus, this Sumbawa Indonesian learning educational game can be a means for parents to introduce Sumbawa language to children and become an interactive learning tool for teachers to students at school. Therefore, having an Android-based Sumbawa Indonesian educational game for early childhood is one way to introduce and preserve the local language